Improvement of cognitive function in wild-type and Alzheimer´s disease mouse models by the immunomodulatory properties of menthol inhalation or by depletion of T regulatory cells - Casares, Noelia; Alfaro, María; Cuadrado-Tejedor, Mar; Lasarte-Cia, Aritz; Navarro, Flor; Vivas, Isabel; Espelosin, María; Cartas-Cejudo, Paz; Fernández-Irigoyen, Joaquín; Santamaría, Enrique; García-Osta, Ana; Lasarte, Juan José (Frontiers in Immunology, 2023)
A complex network of interactions exists between the olfactory, immune and central nervous systems. In this work we intend to investigate this connection through the use of an immunostimulatory odorant like menthol, analyzing its impact on the immune system and the cognitive capacity in healthy and Alzheimer's Disease Mouse Models. We first found that repeated short exposures to menthol odor enhanced the immune response against ovalbumin immunization. Menthol inhalation also improved the cognitive capacity of immunocompetent mice but not in immunodeficient NSG mice, which exhibited very poor fear-conditioning. This improvement was associated with a downregulation of IL-1 and IL-6 mRNA in the brain´s prefrontal cortex, and it was impaired by anosmia induction with methimazole. Exposure to menthol for 6 months (1 week per month) prevented the cognitive impairment observed in the APP/PS1 mouse model of Alzheimer. Besides, this improvement was also observed by the depletion or inhibition of T regulatory cells. Treg depletion also improved the cognitive capacity of the APPNL-G-F/NL-G-F Alzheimer´s mouse model. In all cases, the improvement in learning capacity was associated with a downregulation of IL-1 mRNA. Blockade of the IL-1 receptor with anakinra resulted in a significant increase in cognitive capacity in healthy mice as well as in the APP/PS1 model of Alzheimer´s disease. These data suggest an association between the immunomodulatory capacity of smells and their impact on the cognitive functions of the animals, highlighting the potential of odors and immune modulators as therapeutic agents for CNS-related diseases.